Chronic Administration of Catechin Decreases Depression and Anxiety-Like Behaviors in a Rat Model Using Chronic Corticosterone Injections - Lee, Bombi (The Korean Society of Applied Pharmacology, 2013)
Previous studies have demonstrated that repeated administration of the exogenous stress hormone corticosterone (CORT) induces dysregulation in the hypothalamic-pituitary-adrenal (HPA) axis and results in depression and anxiety. The current study sought to verify the impact of catechin (CTN) administration on chronic CORT-induced behavioral alterations using the forced swimming test (FST) and the elevated plus maze (EPM) test. Additionally, the effects of CTN on central noradrenergic systems were examined by observing changes in neuronal tyrosine hydroxylase (TH) immunoreactivity in rat brains. Male rats received 10, 20, or 40 mg/kg CTN (i.p.) 1 h prior to a daily injection of CORT for 21 consecutive days. The activation of the HPA axis in response to the repeated CORT injections was confirmed by measuring serum levels of CORT and the expression of corticotrophin-releasing factor (CRF) in the hypothalamus. Daily CTN administration significantly decreased immobility in the FST, increased open-arm exploration in the EPM test, and significantly blocked increases of TH expression in the locus coeruleus (LC). It also significantly enhanced the total number of line crossing in the open-field test (OFT), while individual differences in locomotor activities between experimental groups were not observed in the OFT. Taken together, these findings indicate that the administration of CTN prior to high-dose exogenous CORT significantly improves helpless behaviors, possibly by modulating the central noradrenergic system in rats. Therefore, CTN may be a useful agent for the treatment or alleviation of the complex symptoms associated with depression and anxiety disorders.